ANALYSIS OF SLANG AMONG STUDENTS OF SILIWANGI UNIVERSITY - Neng Aropah Wasilah; Zahra Izzatul Jannah; Ichsan Fauzi Rahman (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to analyze the meaning of variations in slang among students. The research method used is the descriptive analysis method which includes surveys and interviews to collect data from a sample of students. Findings show that slang is widely used in everyday interactions, creating group identity and influencing communication norms. This analysis provides insight into how slang plays a role in shaping students' communication culture regarding formal and informal communication. The results of the slang variation data obtained are the words Anjay, Kepo, Gas, Mengcapek, Keren, Melow, Garing, Alay, Kece, Baper, Mager, Mantul, Santuy, Jastip, and Bucin.